2012
DOI: 10.1080/08897077.2011.640220
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Implementing a Multispecialty Graduate Medical Education Curriculum on Screening, Brief Intervention, and Referral to Treatment (SBIRT)

Abstract: The authors sought to evaluate the feasibility and acceptability of initiating a Screening, Brief Intervention, and Referral to Treatment (SBIRT) for alcohol and other drug use curriculum across multiple residency programs. SBIRT project faculty in the internal medicine (traditional, primary care internal medicine, medicine/pediatrics), psychiatry, obstetrics and gynecology, emergency medicine, and pediatrics programs were trained in performing and teaching SBIRT. The SBIRT project faculty trained the resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…32,33 Residents' satisfaction with SBIRT/MI training is important. 34,35 Although prior research implies that shorter MI trainings may produce higher levels of resident satisfaction, 16,23 our results indicate generally high levels of satisfaction with both trainings, while highlighting differences in satisfaction between the trainings. However, it is unclear which variables contributed to the variance between training types, which differed for residency program, race, prior experience with SBIRT, length, and structure, when the trainer and core curriculum were held constant.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…32,33 Residents' satisfaction with SBIRT/MI training is important. 34,35 Although prior research implies that shorter MI trainings may produce higher levels of resident satisfaction, 16,23 our results indicate generally high levels of satisfaction with both trainings, while highlighting differences in satisfaction between the trainings. However, it is unclear which variables contributed to the variance between training types, which differed for residency program, race, prior experience with SBIRT, length, and structure, when the trainer and core curriculum were held constant.…”
Section: Discussionmentioning
confidence: 46%
“…Residents were from 3 separate medical specialties. Although SBIRT trainings have been tested in EM, 36 IM, 16 and PEDS programs with similar results, residents from each specialty may have interpreted the survey differently. Further, because all residents were from a single site, these results may not be generalizable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening, Brief Intervention and Referral to Treatment (SBIRT) is a comprehensive and integrated approach to early intervention and treatment services through universal screening for persons with substance use disorders and those at risk (Babor et al, 2007;Madras et al, 2009). The addition of SBIRT training to residency programme has been shown to greatly improve counselling skills and confidence in these skills (Tetrault et al, 2011). It has also been demonstrated that knowledge and confidence in working with patients for promoting smoking cessation as well as other behavioural change can be improved by brief (1-2 hour) training sessions, including brief web-based intervention (Pederson, Blumenthal, Dever, & McGrady, 2006;Roman, Borges, & Morrison, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…For example, related concepts such as ''interprofessional education'' and ''interdisciplinary collaboration'' were often conflated, with limited conceptual clarity between the two (Oandasan & Reeves, 2005;Reeves et al, 2011). In addition, several addictions education initiatives were deemed ''multispecialty,'' which referred to the involvement of more than one subspecialization within medicine (e.g., family medicine, obstetrics/gynecology, psychiatry; Rasyidi et al, 2012;Tetrault et al, 2012). Although these initiatives do not take the conventional definition of ''interdisciplinary,'' we included these articles because of their clear intent to train a wide range of providers in addiction and because many physicians consider these initiatives ''interdisciplinary'' (Grant, Finocchio, & Pew Health Professions Commission, 1995).…”
Section: Icae Definition and Terminologymentioning
confidence: 98%